2001
DOI: 10.1067/mmt.2001.115266
|View full text |Cite
|
Sign up to set email alerts
|

Posterior disk displacement: Morphologic assessment and measurement reliability—lumbar spine

Abstract: Different disk types demonstrated distinct size averages. Interexaminer agreement was good concerning disk assessment and measurements. Intraexaminer agreement was lower than expected. A millimetric ruler is an acceptable alternative to digital measurement devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Out of 34 studies, only 17 reported reproducibility, and only one of these studies [48] used an appropriate statistical method – in that case, LOA. Eight of the remaining studies [8,33,34,38,48,52,55,57] used ICC, which is a measure of reliability, not agreement [45]. Furthermore, only one out of these eight studies reported an error estimate [55].…”
Section: Discussionmentioning
confidence: 99%
“…Out of 34 studies, only 17 reported reproducibility, and only one of these studies [48] used an appropriate statistical method – in that case, LOA. Eight of the remaining studies [8,33,34,38,48,52,55,57] used ICC, which is a measure of reliability, not agreement [45]. Furthermore, only one out of these eight studies reported an error estimate [55].…”
Section: Discussionmentioning
confidence: 99%
“…Once digitized, the radiographic image is analyzed using a software program which provides measuring tools but still requires the clinician to manually select the fiducial points for measurement [19]. According to Cooley et al [7] a millimetric ruler is an acceptable alternative to digital measurement devices. Regardless of the method used, distortion of the image can occur, leading to erroneous results [31].…”
Section: Discussionmentioning
confidence: 99%